The Potentional Relationship Between Gingival Recession And Bone Thickness In The Context Of Orthodontic Treatment - Adisty Restu Poetri; Shella Indri Novianty (Odonto : Dental Journal, 2023)
Background : The term "gingival recession" describes the downward movement of the gum border in relation to the cemento-enamel junction (CEJ), which is the point where the crown and root of a tooth meet. There are several different factors that might contribute to gingival recession, including as mechanical trauma, orthodontic treatment, or plaque-induced inflammation. Not only do patients receive orthodontic treatment, but also practising dentists do so because they see orthodontic therapy as a crucial part of multidisciplinary dental care. Objective : To discuss the potential relationship between gingival recession and bone thickness in the context of orthodontic treatment. Discussion: Bone thickness is impacted by orthodontic treatment, however bone density is not linked to a higher incidence of gingival recession. The patient's periodontal phenotype, which is determined by genetics, environment, and the way they wash their teeth, is connected to increased gingival recession during orthodontic therapy. Conclusion : There is no potential relationship between gingival recession and bone thickness in the context of orthodontic treatment.